Analisis Akuntabilitas Keuangan pada Kantor Kementerian Agama Dalam Wilayah Provinsi Aceh - Zulfahmi Zulfahmi; Hasan Basri; Darwanis Darwanis (Jurnal Telaah dan Riset Akuntansi, 2016)
The efforts to improve the financial accountability in governmental sector is very important to be taken in order to fulfil society demand. Having a reliable accountability will improve the trust of society as well as other stakeholders toward those who are responsible for it. As a form of government’s accountability in managing the state’s finances, it is very important to the entities of governmental sector to provide financial statements. The purpose of this research is to analyse the accountability in the ministries of religion in Aceh province. This study used descriptive analysis method. The population of this study included all offices working under the Ministry of Religion in the province of Aceh which involved 24 offices. The results of the study indicated that by implementing good and adequate financial accountability components, which accountability for probity and legality, process accountability, performance accountability, programme accountability, and policy accountability, will improve the financial accountability in the ministries of religion in Aceh.KEYWORDS : financial accountability, financial statement, the Ministry of Religion.